Anne arrives - George, K. (Kallie), 1983- (Tundra Books, 2018)
Marilla and Matthew Cuthbert need help on their farm, so they've adopted what they hope will be a sturdy, helpful boy. Instead, Matthew finds Anne awaiting him at the train station -- imaginative, brash, redheaded Anne-with-an-e. With her place at the Cuthberts' at risk -- particularly if nosy neighbor Mrs. Lynde has anything to say about it -- Anne will have to learn patience, understanding and what it takes to make Green Gables her true home. Lovingly adapted by Kallie George with beautiful, nostalgic illustrations by Abigail Halpin, Anne Arrives is perfect for new fans of Anne and old.